Energy Poverty and Subjective Wellbeing: Empirical Analysis in Indonesia - Zetara Zetara; Djoni Hartono (Department of Development Economics, Universitas Sriwijaya, 2023)
As stated in the Sustainable Development Goals, energy poverty is a severe problem that is a priority for the United Nations to eradicate. In general, the study on energy poverty is concerned with objective indicators. More study still needs to evaluate energy poverty with subjective indicators, especially in Indonesia. This study aims to analyze the relationship between energy poverty as measured by the Multidimensional Energy Poverty Index which is proxied by happiness. Based on consumer theory that an individual's utility in meeting their needs will influence their satisfaction, where satisfaction is closely related to happiness, it is hypothesized that there is a relationship between energy poverty, where someone has limited access to energy, which will harm their happiness—estimated using the panel fixed effect method using 17,918 individual data obtained from IFLS4 (2007) and IFLS5 (2014) survey data. These findings suggest that energy poverty is detrimental to personal happiness. Using firewood for cooking, not having access to electricity, and not having a refrigerator or TV are signs of low energy and significantly impact happiness. Access to energy is very influential in making everyday life easier, increasing productivity and quality of life for individuals.